ANALISIS EFEKTIVITAS DAN EFISIENSI PENDAPATAN ASLI DAERAH TERHADAP KEMANDIRIAN PEMERINTAH KABUPATEN ALOR - Zainudin Adang Djaha (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2021)
The community as a control function on regional development has the right to know the regional financial capacity through the effectiveness and efficiency of Regional Original Revenue. The effectiveness and efficiency of PAD revenue will provide regional financial independence, furthermore regional financial independence in the implementation of regional development will support regional financial performance. The formulation of the problem includes: How is the Effectiveness of Regional Original Revenue on the Independence of the Alor Regency Government, How is the Efficiency of Regional Original Revenue on the Independence of the Alor Regency Government; While the objectives include Knowing the Effectiveness of Regional Original Revenue on the Independence of the Alor Regency Government, Knowing the Efficiency of Regional Original Income on the Independence of the Alor Regency Government. The data analysis technique used in this research is quantitative descriptive using the formula of effectiveness ratio, efficiency ratio and regional independence constellation. The results of the study indicate that the effectiveness of the realization of regional income as stated in the Regional Revenue and Expenditure Budget (APBD) of the Alor Regency Government starting from 2019 - 2020 is in the Very Effective category. The realization of costs for obtaining revenue at the Kupang Regency Government in 2019 - 2020 is included in the efficient category, namely the achievement of realization of collection fees to obtain regional income is between the standard efficiency achievements of 10% - 20% where for 2019 the realization of collection costs to obtain revenue is achieved. regional financial independence ratio of 19.44%, and the achievement of the realization of collection fees to obtain regional income in 2020 of 14.89%, the ratio of regional financial independence in 2019 of 17.27%, the ratio of regional financial independence in 2020 of 11.94%, The results of achieving the ratio of regional financial independence from 2019 to 2020 is considered very low.